Culture and Communication in Thailand - Malikhao, Patchanee (Springer Singapore : Imprint: Springer, 2017)
This book features research papers that examine a host of contemporary issues in Thailand. Coverage includes culture, gender violence, tourism, human trafficking, environmental and ecological issues, sustainability and the sufficiency economy, the (mis)handling of elephants, and more. It features a sociological and anthropological perspective with a dash of communication for sustainable social change. The papers investigate the various phases of communication technology and its impact on cultural change in the country. They explore the use of social networks and privacy issues as well as ethical journalism in the contexts of Thai Buddhism, Thai culture, and other enabling environmental factors. The contributors focus on documentary research of both quantitative and qualitative data on Thai social change as a consequence of globalization and digital technology. They first provide a general overview of social media and communication in the country. Next, the authors go on to explore the specifics of digital communication. This includes a look at its impact on the various ways of Thai communication given politico-economic and religious influences.
Keywords: Social sciences.; Culture -- Study and teaching.; Cultural studies.; Communication.; elektronické knihy; electronic books